Translating the Qur'an in Indonesia: Marrying the Concept of Transcreation and Critical Discourse Analysis - Gunawan, Fahmi; Batmang, Batmang; Boulahnane, Saad (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Despite the growing concerns of research discussing transcreation in translation studies from various perspectives, little empirical evidence reported the transcreation in Quranic translation as a religious sacred text. To fill this void, the present study aims to elucidate Qur'an translation in Indonesia from the perspective of trancreation and critical discourse analysis. The data were collected via observation of translations of Quranic verses which contain transcreation. The findings suggest that Quranic translation as a religious sacred text encompasses extensive transcreation. It took the form of words, phrases, and clauses—units used to create a discourse in upholding Islamic law and exclusivism in Indonesia. The discourse of Sharia law enforcement was attributed to situational, institutional, and social factors. This empirical study implies that transcreation in the sacred text is unavoidable due to the translators' ideology and socio-cultural background differences and creates a metanarrative on the importance of mutual respect, tolerance, and interfaith dialogue.